THE RELATIONSHIP BETWEEN SPORTS ACTIVITY HABITS AND WORKSITE HEALTH PROMOTION AMONG EMPLOYEES WORKING IN THE PUBLIC ADMINISTRATION, DEFENCE AND SOCIAL SECURITY SECTORS - Hidvégi, Péter; Pucsok, József Márton (Stadium - Hungarian Journal of Sport Sciences, 2024)
Growth in the economy and production, as well as increased labor burdens, have led to an increase in the number of occupational health, including accidents at work and occupational diseases. As the first steps of the methodology described in international models, this research facilitates the steps of assessment and evaluation, followed by planning, among individuals, organizations and the supporting environment. Within the framework of the series of surveys, we assessed, among others, the sports activity of workers in the sectors of public administration, defense and compulsory social security. Our hypothesis that the majority of employers (at least 70%) provide health promotion according to employees has not been confirmed. More than a third of worksites (37.9%) provide health promotion opportunities based on employee responses. Based on the results obtained, comprehensive proposals can be formulated that can be useful to employers, employees and actors in the supportive environment.